La promoción de la inclusión de estudiantes con dificultades de aprendizaje en el aula de educación básica superior - Quinde Méndez, Mallerly Noelia (2025)
The main objective of this research was to promote the inclusion of students with learning difficulties in the regular classroom of Upper Basic Education through the development of a psychopedagogical strategy proposal. The study was conducted at the “Quevedo” Educational Unit. Using a mixed-methods approach, surveys were applied to students, interviews were conducted with teachers, and direct classroom observations were made. This allowed the identification of multiple barriers to educational inclusion, such as the lack of adapted teaching resources, limited implementation of inclusive strategies, and the presence of exclusionary attitudes among some peers. The results showed that pedagogical practices persist which hinder the active participation of students with learning difficulties, generating negative effects on their academic performance, self-esteem, and social integration. Likewise, the need to transform the school environment into a more equitable, collaborative, and diversity-respecting space was evidenced. In response to these findings, a single psychopedagogical strategy was designed aimed at fostering an inclusive educational environment. The proposal includes collaborative activities, curricular adaptations, and the use of accessible technological resources, with the purpose of ensuring equity, mutual respect, and meaningful learning in the classroom. In conclusion, it is established that a well- structured psychopedagogical strategy, focused on diversity and adapted to the specific context, can become an effective tool to promote inclusion.